From Monster to Ancestor: The Emergence and Animation of the Deep Past - Richard Somerset (Cahiers Victoriens et Edouardiens)
This article looks at the treatment of extinct species by scientific popularisers in the nineteenth century, and seeks to show how their status changed over time, and why. Starting out as exotic otherworldly monsters, they retained this status amongst those authors seeking to present the findings of palaeontology as consistent with the Biblical narrative of creation, while authors willing to envisage an alternative natural history of creation tended to naturalise them. By the end of the century, however, the relationship had become more complex, with authors seeking to balance similarity and otherness, and using the mix as a way of naturalising their preferred reading of the ‘story’ of evolutionary processes. The article thus shows how the changing relationships between the categories of ‘monster’, ‘animal’ and ‘man’ reflected the strategies of educators for dealing with a perceived existential crisis for man and his relationship to the natural world.